The Effectiveness of the National Narcotics Agency (BNN) in Preventing and Controlling Drug Trafficking in Rokan Hilir Regency - Alexander, Alexander; Abidin Pakpahan, Zainal; Siahaan, Nimrot (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The aim of this research is to determine the effectiveness of the Rokan Hilir National Narcotics Agency (BNN) in preventing and controlling drug trafficking in the Rokan Hilir area. The type of research used is descriptive qualitative research. The results of the discussion show that the prevention and control of drug trafficking carried out by the Rokan Hilir National Narcotics Agency is effective. This can be seen from several drug trafficking cases that were successfully uncovered by BNN Rokan Hilir. Several cases that have been uncovered and handled by BNN Rokan Hilir are cases of illicit narcotics trafficking. In 2023, officers confiscated 20.6 kilograms of crystal methamphetamine. For his actions, the suspect is threatened with Article 114 paragraph 2 in conjunction with Article 132 paragraph (1) 112 paragraph 2 in conjunction with Article 132 paragraph (1) of Law Number 35 of 2009, with a maximum penalty of the death penalty. 2019BNN also succeeded in arresting a suspected dealer of 4.1 kg of methamphetamine and 10 thousand ecstasy pills. This proves that the National/City Narcotics Agency is working effectively in carrying out drug control and prevention in the Rokan Hilir area.